2016
DOI: 10.1002/iub.1475
|View full text |Cite
|
Sign up to set email alerts
|

Targeting glioblastoma stem cells (GSCs) with peroxisome proliferator‐activated receptor gamma (PPARγ) ligands

Abstract: Glioblastoma multiforme (GBM), also known as glioblastoma, is the most common and aggressive brain tumor. GBM has a poor survival rate and high resistance to standard therapy, leading to recurrence and metastasis to adjacent normal regions. Glioblastoma stem cells (GSCs) are regarded as an emerging target for therapy of GBM. Peroxisome proliferatoractivated receptor gamma (PPARc) is a nuclear receptor that functions in a variety of cancers and in normal adipocyte differentiation. The newly discovered connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…We also found that A172 and U87 glioblastoma cells express PPAR γ using western blotting analysis. Hence, its ligands have been suggested as potential targets for glioblastoma stem cells [35]. Our findings provide a BIS- and 14-3-3 gamma-mediated inhibitory mechanism for the GSC-like sphere system suggesting the potential of combination therapy targeting GSCs via the manipulation of the BIS and/or 14-3-3 gamma/SOX2 axis in which STAT3 and AKT function upstream.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We also found that A172 and U87 glioblastoma cells express PPAR γ using western blotting analysis. Hence, its ligands have been suggested as potential targets for glioblastoma stem cells [35]. Our findings provide a BIS- and 14-3-3 gamma-mediated inhibitory mechanism for the GSC-like sphere system suggesting the potential of combination therapy targeting GSCs via the manipulation of the BIS and/or 14-3-3 gamma/SOX2 axis in which STAT3 and AKT function upstream.…”
Section: Discussionmentioning
confidence: 68%
“…Previously, we established a GSC-like sphere culture system in which SOX2 was expressed at significant levels [34] and hypothesized that PPAR γ ligands may affect cancer stemness and induce apoptosis in GBM [35]. In this study, we describe the effect of a combination treatment with PPAR γ ligands and its inhibitor GW9662 on spheres of glioblastoma cells through downregulation of BIS and 14-3-3 gamma levels, as well as inhibition of SOX2, MMP2 activity, and sphere-forming activity without enhancing the levels of cleaved poly(ADP-ribose) polymerase (PARP).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Garros-Regulez et al found that TMZ resistance was positively correlated with SOX2 expression in glioblastoma cells and in cells expressing high levels of SOX2 [24]. When we tested this in our culture system, we also consistently observed that SPs expressing SOX2 [15,25] were more resistant to TMZ treatment compared with ML cells, suggesting that our culture system is suitable for in vitro study of GSCs and the drug response [26]. Based on this, we examined the effect of BIS or HSF1 depletion in combination with TMZ treatment, and found that apoptosis was increased (as measured by PARP cleavage), SOX2 levels were decreased, and SP formation was increased.…”
Section: Discussionmentioning
confidence: 72%
“…HDAC inhibitors have been reported to be potent differentiation agents in GSCs, reducing GBM growth mainly by inducing cell necrosis and growth arrest (Tung et al, 2018). Also, a cell cycle inhibitor (Tachon et al, 2018), a dopamine receptor antagonist (Dolma et al, 2016), an adrenergic receptor antagonist (He et al, 2017), a VEGFR inhibitor (Kalpathy-Cramer et al, 2017), a PPAR receptor agonist (Im, 2016;Gupta et al, 2018), a PI3K inhibitor (Zhao et al, 2017), mTOR inhibitors (Friedman et al, 2013), a lipoxygenase inhibitor (Zappavigna et al, 2016), and an HMGCR inhibitor (Hamm et al, 2014) have been shown to exhibit anticancer effects on GBM cells, some of which have been shown to target GSCs. Our findings are expected to facilitate the development of antitumor strategies that specifically target GSCs and pave the way for the treatment of cancer resistance.…”
Section: Discussionmentioning
confidence: 99%